Teachers' approaches to music performance anxiety management: a systematic review - Mazzarolo, Isabella; Burwell, Kim; Schubert, Emery (Frontiers in Psychology, 2023)
Performance anxiety is a widespread issue that can affect musicians across their education and career. It can develop in musicians from a young age leading to short-term and long-term impacts on not only their performance, but also their well-being. There is potentially a significant role that music educators hold in the development of their students and how they handle performance anxiety, though it is not clear how, or how often, teachers support their students in this way. Through a PRISMA-based systematic review, this paper explores what is known about the strategies used by music educators to help manage their students' performance anxiety. The paper also discusses the role that instrumental/vocal tutors and school classroom teachers might hold in this area. The findings show that music educators are implementing multiple strategies to assist their students with MPA, with the most common being simulated performance, positive outlook, preparation and breathing. It was found that there is a role for teachers to address MPA management with their students. While some students prefer to receive MPA support from experts in the field of psychology, students still expressed a need to have this support come from their teacher. Though many teachers felt a need for additional training for them to help their students cope with MPA, many of the strategies were found to be multifunctional and embedded into the regular teaching practices or teaching styles of the educator. Although these strategies might be implicit rather than explicit, the findings suggest that music educators could represent a valuable source of support for MPA management.